Solution conformations of a linked construct of the Zika virus NS2B-NS3 protease - Mahawaththa, Mithun C.; Klein, Christian D. (Antiviral research, 2017)
The Zika virus presents a serious risk for global health. Crystal structures of different constructs of the Zika virus NS2B-NS3 protease (NS2B-NS3pro) have been determined with the aim to provide a basis for rational drug discovery. In these structures, the C-terminal β-hairpin of NS2B, NS2Bc, was observed to be either disordered (open conformation) or bound to NS3pro complementing the substrate binding site (closed conformation). Enzymatically active constructs of flaviviral NS2B-NS3 proteases commonly used for inhibitor testing contain a covalent peptide linker between NS2B and NS3pro. Using a linked construct of Zika virus NS2B-NS3pro, we studied the location of NS2Bc relative to NS3pro in solution by pseudocontact shifts generated by a paramagnetic lanthanide tag attached to NS3pro. Both closed and open conformations were observed with different inhibitors. As the NS2B co-factor is involved in substrate binding of flaviviral NS2B-NS3 proteases, the destabilization of the closed conformation in the linked construct makes it an attractive tool to search for inhibitors that interfere with the formation of the enzymatically active, closed conformation.